Дослідження стійкості багатошарових пластин з отворами складної форми за допомогою теорії R-функцій та варіаційних методів - Курпа, Лідія Василівна; Ткаченко, Вікторія Валеріївна; Шматко, Тетяна Валентинівна (Інститут прикладних проблем механіки і математики імені Я. С. Підстригача НАН України, 2018)
The laminated plates with cuts of a complex form are studied with meshless approach, based on combined application of the R-functions theory and variational methods. The proposed method is developed for thin plates of an antisymeric form along thickness. Mathematical formulation is presented within the framework of classical nonlinear theory of plates using Kirgoff-Love’s hypothesis. In order to investigate the laminated plates with a complex cut and different boundary conditions, the corresponding solution structures and admissible functions were constructed. The software was developed and tested on many problems. In particular, the obtained results were compared with available ones for a cross three-layered plate with free rectangular cut. For plates with cuts of a complex form effect of different geometrical and physical parameters was stydied. Various types of fastening, geometry of the plate and different materials properties are considered. The nondimensional buckling load, instability regions and response curves are presented for plates with complex form of cut.
Investigation of the stability of laminated plates with cuts of a complex shape by the R-functions theory and variational methods
Keywords: навантаження критичне; коливання параметричні; стійкість динамічна